The Role of Religious Leaders in Conflict Resolution in Papua - Rano M.A. Tilaar (Goodwood Publishing, 2026)
Purpose: This study examines the role of religious leaders in conflict resolution in Papua, focusing on their strategies and social legitimacy in mediating relationships among communities, the government, and armed groups. Research Methodology: This study employed a qualitative approach grounded in conflict resolution theory and local actor-based peacebuilding perspectives. Data were collected through field observations, limited participation, and in-depth interviews with church leaders, Muslim figures, and indigenous customary leaders who were involved in mediation and peace. The data were analyzed qualitatively using an ethnographic approach involving systematic coding and thematic interpretation to identify patterns related to mediation strategies, social legitimacy, and trust-building processes. Results: The findings indicate that religious leaders serve as trusted moral mediators within their communities. Their roles include facilitating dialogue, advocating for humanitarian concerns, maintaining informal communication across conflicting parties, and strengthening social cohesion through religious activities and peace education. Their community-based authority enables them to operate effectively in a polarized conflict setting. Conclusions: Religious leaders remain important actors in advancing reconciliation and supporting sustainable peace in Papua. Their moral authority and strong community ties allow them to maintain dialogue and foster trust, despite ongoing political and security challenges. Limitations: Limited access to certain conflict areas and the relatively small number of participants may have affected the broader applicability of the findings. Contributions: This study contributes empirical insights into the role of locally embedded religious actors in peacebuilding processes within plural and conflict-affected societies.